Why are some people in the UK reluctant to seek support for their pets? - Janine C Muldoon; Joanne M Williams (Animal Welfare, 2024)
Drawing upon data from a study examining experiences of accessing support for pets from the UK animal welfare charity Blue Cross, this paper illuminates reasons why people might not seek support when they need it. This applies to those who are struggling financially and are eligible for, but do not take, free/reduced cost veterinary care, or are having other problems (e.g. the animal’s disruptive behaviour or ill health, struggling to care for the pet due to changing circumstances or health problems, or coping with pet loss). Twenty Blue Cross service users (15 female, five male, age 29–67) took part in individual online interviews using a semi-guided narrative approach, where they were encouraged to share their experiences of reaching out. They were also asked to reflect upon why others may not do the same, and if they had any recommendations for organisations to help them reach these people. Findings echo other studies that highlight a fear of being judged, disclosure and stigma. Guilt, shame, lack of awareness, financial concerns, and wanting to manage independently, all play important roles. These factors have implications for the way support services are advertised and delivered to ensure animals receive the care needed. We describe these reflections and recommendations and identify three broader ideological narratives underpinning participants’ stories: ‘giving back’; ‘equity’, and ‘sacrifice’. These reveal how wider societal attitudes and values shape identities and behaviours. It is vital that support on offer is reframed to explicitly counteract these influences to ensure optimal animal and human welfare.